1150-P: Impact of Angiotensin-Converting Enzyme Inhibitors or Angiotensin Receptor Blockers on Renal Outcomes in Patients with Type 2 Diabetes and Proteinuria - COLEMAN, CRAIG I.; WEEDA, ERIN R.; KHARAT, AKSHAY A.; BOOKHART, BRAHIM; BAKER, WILLIAM L. (Diabetes (New York, N.Y.), 2019)
Background: The impact of angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) on renal outcomes in patients with type 2 diabetes (T2D) and proteinuria remains unclear. Methods: A search of Medline, Embase and the Cochrane Databases through 11/2/2018 was performed. We included randomized controlled trials (RCTs) of T2D patients and micro- or macroalbuminuria; comparing an ACEI or ARB with placebo, placebo+background antihypertensives or non-ACEI or ARB containing antihypertensives; randomizing ≥100 subjects; and following subjects for ≥12 months. Endpoints included doubling of serum creatinine (SCr), end-stage renal disease (ESRD), all-cause and cardiovascular (CV) mortality and progression and regression of proteinuria. A Hartung-Knapp random-effects model producing a risk ratio (RR) with 95% confidence interval (CI) was employed, with between-study variance calculated using the Paule-Mandel estimator. Results: The use of an ACE inhibitor or ARB was not associated with a significant reduction in the risk of a doubling in SCr (n=7 trials, RR=0.77, 95% CI=0.50-1.21). ACE inhibitors or ARBs reduced the risk of progressing to ESRD (n=8, RR=0.79, 95CI=0.75-0.83). No difference in all-cause (n=11, RR=0.98, 95% CI=0.89-1.08) or CV mortality (n=6 trials, RR=1.08, 95% CI=0.92-1.28), nor the composite outcome of doubling SCr, development of ESRD or mortality (n=3 trials, RR=0.87, 95% CI=0.72-1.06) were observed. The risk of progression of patients’ proteinuria was decreased when an ACE inhibitor or ARB was used versus control (n=10, RR=0.49, 95% CI=0.33-0.74). The chance of regression of patients’ proteinuria was not significantly improved with an ACE inhibitor or ARB (n=11, RR=1.55, 95% CI=0.93-2.58). Conclusion: ACEIs and ARBs may reduce the risk of ESRD and slow progression of nephropathy, but do not appear to decrease all-cause or CV mortality in T2D patients with proteinuria.